Nitrogen management in relation to wheat (Triticum aestivum) residue management in rice (Oryza sativa) - SHARMA, S N (The Indian Journal of Agricultural Sciences, 2014)
A field experiment was conducted during the rainy seasons of 1995 and 1996 at the Indian Agricultural Research Institute, New Delhi, to study the effect of application of a part nitrogen intended for rice (Oryza sativa L.) at the time of incorporation of wheat (Triticum aestivum L. emend. Fiori & Paol.) residue in a rice-wheat cropping system. Application of 40 kg N/ha (one-third of the total dose for rice) at the time of wheat residue incorporation, 40 kg N/ha at transplanting and the rest 40 kg N/ha at panicle initiation increased the grain yield by 0.5-0.7 tonnes/ha, straw yield by 0.5-1.0 tonne/ha, N uptake by 10 kg/ha, apparent N recovery by 10% and agronomic efficiency of N by 5-7 kg grain/kg fertilizer-N over no nitrogen application at the time of incroporation of wheat residue and 60 kg Nlha each at transplanting and panicle initiation of rice. Fertilizer N applied along with wheat residue was better conserved and resulted in higher available N content in soil than N applied after rice transplanting. Advantage of incorporation of wheat residue over its removal or burning was seen only when 40 kg N/ha was applied at the time of its incorporation.